Stagnansi Keterpilihan Perempuan dalam Pemilu Indonesia: Sebuah Literature Review: The Stagnation of Women's Electability in Indonesian Elections: A Literature Review - Fitriani Abbas; Andy Arya Maulana Wijaya; Herman Lawelai; L.M Azhar Sa'ban; Hazel Jovita (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This study conducted a literature review study of articles on women's acceptability in elections in Indonesia, by analyzing around n = 299 articles from Scopus data base in the publication period of 2004 to 2022. The data obtained is then processed through the VOS Viewer software application as a data analysis tool, with some of the main menus used from VOS Viewer software (density visualization and overlay) so that visualization of features on the theme of the article related to women's acceptability in Indonesia is obtained. This bibliometric analysis Research shows that obtained articles that discuss women's electability in elections in Indonesia are quite varied although no one is so dominant, the dynamics of women's choice in a number of articles between 2004 to 2022 are not so specific about placing the issue of women's choice in the results of their research. However, this study can explain that women's electability in Indonesian elections is still strongly influenced by demands for women's representation policies, religious identity to Political liberalization through gender equality, gender gaps and women's social status. Therefore, the results of this study show that analysis through literature review will be very helpful and contribute to analyzing the achievements of women's political work in Indonesia.